Optimalisasi Budidaya Perikanan Melalui Digital Marketing di Panti Rehabilitasi Pondok Tetirah Dzikir - Lokita, Raden Arditya Mutwara; Bela Fataya Azmi; Sri Mulyatun; Rahma Widyawati; Rufki Ade Vinanda; Muh. Idris Purwanto (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Jakarta, 2025)
Pondok Tetirah Dzikir Rehabilitation Center is a pesantren (Islamic boarding school) for people with mental disorders (ODGJ) and drug addicts, located in Berbah, Sleman. Established around 1999, the foundation of Pondok Tetirah Dzikir was driven by the concern of the caretakers for individuals with mental health issues. The main activity at the center involves regular dhikr (remembrance of God) five times a day after obligatory prayers, practiced by the residents who consist of ODGJ and drug addicts. The community recognizes the center as a free rehabilitation facility, even though it still requires funding to meet the daily needs of its approximately 170 residents. Providing basic necessities, such as three meals a day, presents a significant challenge due to financial constraints. The primary problem faced by the center is a lack of funding. To address this, a community service team from Universitas Amikom Yogyakarta conducted a training program titled